Stern wheel steamer HANNAH tied up to riverbank, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: 6218 On verso of image: Steamer Hannah The HANNAH was built in 1898 by the Howard shipyard at Jeffersonville, Indiana, using molds from the Ohio River boats BLUFF CITY AND DOLPHIN NO. 3. Along with her sister ships SUSIE AND SARAH, she was shipped in sections to Unalaska, where she was assembled by the Alaska Commercial Co. and proceeded from there to St. Michael and the Yukon under her own power. They were spectacular boats in the grand tradition of the Western river packets, particularly at night when they made their fast passages up and down the desolate Yukon with decks and cabins ablaze with lights. Their niceties included spacious mahogany paneled dining salons and two and three-berth staterooms to accommodate 150 first-class passengers. (pg. 29) Notes from Gordon Newell, ed., The H.W. McCurdy Marine History of the Pacific Northwest (Seattle: Superior Publishing Co, 1966). To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number